2007
DOI: 10.1080/13693780701299333
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicansAls proteins mediate aggregation with bacteria and yeasts

Abstract: Candida albicans occupies a microniche on mucosal surfaces where diverse microbial populations interact within a biofilm. Because C. albicans is intimately involved with other microbes in this environment we studied the interactions of C. albicans with other fungi and bacteria that form mixed microbial aggregates. Once aggregation is initiated, aggregates form rapidly and incorporate fungal as well as bacterial cells. The fungus formed mixed microbial aggregates with homotypic cells (i.e., self to self, e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 27 publications
6
83
0
3
Order By: Relevance
“…Among them, mannans could be one of the potential surface ligands because these polysaccharides are particularly abundant at the outermost layer (Gow et al 2012). However, the composition and molecular architecture of the cell wall of C. albicans are quite complex (Klotz et al 2007;Li and Palecek 2008), and other surface-associated glycoproteins and adhesins (e.g., Als and Eap1) potentially interact with GtfB. Clearly, further studies are needed to identify the binding partners as well as their spatial localization on the fungal surface that mediates GtfB-C. albicans adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, mannans could be one of the potential surface ligands because these polysaccharides are particularly abundant at the outermost layer (Gow et al 2012). However, the composition and molecular architecture of the cell wall of C. albicans are quite complex (Klotz et al 2007;Li and Palecek 2008), and other surface-associated glycoproteins and adhesins (e.g., Als and Eap1) potentially interact with GtfB. Clearly, further studies are needed to identify the binding partners as well as their spatial localization on the fungal surface that mediates GtfB-C. albicans adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…S. gordonii also binds to C. albicans Als5 (27). Other Grampositive cocci, including Staphylococcus aureus, Staphylococcus epidermidis, and Streptococcus pyogenes, also adhere to C. albicans (44).…”
Section: Als3 Functionmentioning
confidence: 99%
“…118,119 An in vitro model of various C. albicans-bacterial biofilms concluded that bacteria negatively impact C. albicans biofilm formation by inhibiting fungal growth and suppressing genes responsible for hyphae formation. 120 Peleg et al 121 described 5 types of bacterial-fungal interactions and many speculate these also take place within the vagina: physical interactions, 122,123 chemical exchanges, 124 use of metabolic byproducts, 109,118 changes in the environment, 124 and alteration of the host immune response. 125 Further studies are required to better understand this important relationship between vaginal bacteria, Candida spp.…”
Section: 100mentioning
confidence: 99%
“…Interactions between Candida and microbiota at the mucosal interface have profound effects on the vaginal ecosystem. 109,[120][121][122][123][124][125] Metabolites and small molecules made by the microbiota affect the metabolism and morphology of Candida species. Changes in microbiota relative abundance also impact the abundance of Candida and its ability to access the mucosal surface, where invasion occurs.…”
Section: Importance Of the Fungal Mycobiomementioning
confidence: 99%